South African ostrich industry : taking control of Its own destiny - Grant-Makokera, Catherine; Townsend, Stephanie (London : Wits Business School, 2020)
In early 2020, CEO of the South African Ostrich Business Chamber (SAOBC), Piet Kleyn, and the SAOBC industry veterinarian, Dr Adriaan Olivier, considered the way the ostrich industry had dealt with its challenges over recent years. In response to difficulties, such as avian influenza (avian flu), that affected the industry's export activities negatively, and in the absence of sufficient government support, the industry had put solutions in place in its private capacity. However, operating privately was proving to be costly, as expenses rose every year. It had cost the SAOBC R4.5 million in 2019. Kleyn and Olivier wondered whether self-regulating the ostrich industry was sustainable into the future.
Originally Published InMakokera, C.G., & Townsend, S. (2020). South African Ostrich Industry: Taking Control of its Own Destiny. WBS-2020-4. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Ostrich products industry -- South Africa; Industries-Self-regulation.